Temperature measurements during friction stir welding. Issue 9 (February 2017) - Silva, A.; Backer, J.; Bolmsjö, G.
Abstract The increasing industrial demand for lighter, more complex and multi-material components supports the development of novel joining processes with increased automation and process control. Friction stir welding (FSW) is such a process and has seen a fast development in several industries. This welding technique gives the opportunity of automation and online feedback control, allowing automatic adaptation to environmental and geometrical variations of the component. Weld temperature is related to the weld quality and therefore proposed to be used for feedback control. For this purpose, accurate temperature measurements are required. This paper presents an overview of temperature measurement methods applied to the FSW process. Three methods were evaluated in this work: thermocouples embedded in the tool, thermocouples embedded in the workpiece and the tool-workpiece thermocouple (TWT) method. The results show that TWT is an accurate and fast method suitable for feedback control of FSW.